Towards a unified terminology for angiosperm reproductive systems - Cardoso, João Custódio Fernandes; Viana, Matheus Lacerda; Matias, Raphael; Furtado, Marco Túlio; Caetano, Ana Paula de Souza; Consolaro, Hélder; Brito, Vinícius Lourenço Garcia de (Acta Botânica Brasílica, 2018)
ABSTRACT Angiosperms display an enormous diversity of forms, functions and strategies when it comes to reproduction. This multiplicity has been translated into several terminological concepts and contexts, which have facilitated further research. On the other hand, the use of terms that address the reproduction of flowering plants has been shown to be inconsistent in the literature, complicating communication among specialists. Key terms, such as “reproductive system”, “mating system” and “sexual system”, among others, have been frequently cited as synonyms, and even used in different circumstances. This review proposes to establish a consistent nomenclatural classification in the field of angiosperms reproductive biology in order to facilitate communication among researchers. Specific terms related to angiosperm reproduction are conceptualized and distributed into five general systems: four related to sexual reproduction (sexual, floral, incompatibility and mating systems); and one related to asexual reproduction (apomictic systems). Our proposal is not to establish a natural classification, but rather to provide a general overview of the main concepts that were grouped here in an artificial and functional manner. Our aim is to advance the field of reproductive biology of angiosperms with consistent and well-defined applications of relevant terminologies.